DEVELOPING THE "FAMILY-STUDENT-EDUCATION INSTITUTION" COOPERATION MECHANISM AS A CONDITION FOR ENHANCING THE EFFECTIVENESS OF MEDICAL EDUCATION - Sultanov Qudratillo Ismoilovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article explores the significance and effectiveness of the cooperation between families and educational institutions in enhancing the quality of medical higher education. It highlights how moral and psychological support, active parental involvement in the educational process, and the impact of family environments contribute to students' professional development and academic success. Cooperation between families and educational institutions plays a crucial role in developing students' independent thinking, socio-emotional growth, and motivation for professional activity. The article examines the theoretical and practical aspects of this cooperation mechanism and its role in improving the overall educational system.